An Integrative Model of Logistics Performance: Examining the Role of Customer Satisfaction in Linking Vendor Performance, Pricing Strategy, and Service Quality - Bambang Lukmanul Hakim; Agus Purnomo; Melia Eka Lestiani (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The rapid development of the logistics and courier service industry, along with the growth of e-commerce, requires companies to continuously improve operational performance and service quality. The logistics performance of courier services is influenced not only by internal factors but also by the integration of vendor performance, pricing strategy, and service quality, all of which contribute to shaping customer satisfaction. This study aims to analyze the effect of vendor performance, pricing strategy, and service quality on customer satisfaction and logistics performance, as well as to examine the role of customer satisfaction as a mediating variable in courier service companies in Riau Province. This study employed a quantitative approach using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The research data were collected through questionnaires distributed to 150 users of courier services. The variables analyzed include vendor performance, pricing strategy, service quality, customer satisfaction, and logistics performance. The results indicate that vendor performance, pricing strategy, and service quality have positive effects on customer satisfaction. Service quality has the most dominant influence on customer satisfaction, followed by pricing strategy and vendor performance. Customer satisfaction also has a positive effect on logistics performance. In addition, customer satisfaction serves as a partial mediating variable in the relationship between vendor performance, pricing strategy, service quality, and logistics performance. The non-linear analysis further reveals that the quadratic effects of service quality, pricing strategy, and vendor performance have significant negative effects on customer satisfaction, indicating the presence of a diminishing return effect in which increases in these variables beyond a certain threshold no longer lead to proportional increases in customer satisfaction. This study concludes that improving the logistics performance of courier service companies can be achieved through the integration of vendor operational performance, customer value-based pricing strategies, and enhanced service quality in order to create sustainable customer satisfaction.